(untitled) (Texas Journal of Medical Science, 2025)
This study presents a retrospective analysis of the abdominal form of HenochSchönlein purpura (HSP) in pediatric patients treated at the Multidisciplinary Medical Center of the Tashkent Medical Academy between 2020 and 2024. The aim was to determine the prevalence, clinical characteristics, and complication rates associated with this variant. Among 124 children diagnosed with HSP, 43.5% exhibited abdominal symptoms, including colicky pain, vomiting, and gastrointestinal bleeding. In nearly one-third of these cases, abdominal symptoms preceded the appearance of skin purpura, complicating early diagnosis. Abdominal ultrasonography proved useful in identifying intestinal wall thickening and mesenteric lymphadenopathy. Intussusception occurred in 9.3% of patients, with one case requiring surgical intervention. The study highlights the need for heightened clinical vigilance and the use of imaging tools in pediatric patients with acute abdominal symptoms to improve early diagnosis and prevent severe complications.